2015
DOI: 10.1039/c5nr02837j
|View full text |Cite
|
Sign up to set email alerts
|

SnO2quantum dots decorated on RGO: a superior sensitive, selective and reproducible performance for a H2and LPG sensor

Abstract: We report the H2 and LPG gas sensing behavior of RGO/SnO2 QDs synthesized by a surfactant assisted hydrothermal method. The RGO/SnO2 QD based sensor shows a high response of ∼89.3% to H2 and ∼92.4% to LPG for 500 ppm test gas concentration at operating temperatures of 200 °C and 250 °C, respectively. Further, the RGO/SnO2 QD based sensor shows good selectivity for H2 and LPG in the presence of other interfering gases such as ammonia, chloroform, toluene, benzene, acetone, n-butylacetate, acetic acid and formic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…5b). It is demonstrated that the SnS 2 -SnO 2 -6/RGO sample has a large mesopore centred mainly at 3.98 nm, suggesting that some parts of the small holes have collapsed (Mishra et al, 2015). The smaller poresize mesoporous structure in SnS 2 -SnO 2 -6/graphene facilitate photon diffusion to active sites with less resistance, leading to efficient separation of photo-generated holes and electrons, which is conducive to the improvement of photocatalytic performance (Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 98%
“…5b). It is demonstrated that the SnS 2 -SnO 2 -6/RGO sample has a large mesopore centred mainly at 3.98 nm, suggesting that some parts of the small holes have collapsed (Mishra et al, 2015). The smaller poresize mesoporous structure in SnS 2 -SnO 2 -6/graphene facilitate photon diffusion to active sites with less resistance, leading to efficient separation of photo-generated holes and electrons, which is conducive to the improvement of photocatalytic performance (Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 98%
“…Hydrothermal is one of the commonly reported techniques for preparing metal oxide nanoparticles-rGO composites. Among different metal oxides, SnO 2 nanoparticles were reported extensively to prepare nano-hybrid with rGO for efficient gas sensing application [33][34][35][36][37][38][39][40][41][42]. SnO 2 /rGO [33][34][35] nano-hybrid was prepared by facile hydrothermal treatment where precursor was prepared with mixture of SnCl 4 , HCl, H 2 O, and GO (or rGO).…”
Section: Synthesis Of Graphene/0-d Metal Oxides Compositesmentioning
confidence: 99%
“…Different weight% (0.5-5 wt.%) of Au was added in the SnO 2 /rGO nanocomposite by using HAuCl 4 salt to study the effect of Au concentration on the sensitivity of SnO 2 /rGO gas sensors [34]. Scanning electron micrograph (SEM) of SnO 2 /rGO films which was used for promising gas sensing application are represented in Figure 1 [36]. Ghosh et al [37] reported SnO 2 nanoparticle synthesis by hydrothermal method and SnO 2 /rGO film synthesis by mixing of SnO 2 nanoparticles with GO.…”
Section: Synthesis Of Graphene/0-d Metal Oxides Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been considerable efforts to improve sensors’ performance under extreme conditions, such as using nanostructured materials with ultra-high surface-to-volume ratios, appropriate element doping, surface decoration with noble metals and construction of heterostructure6789. Among them, heterostructure materials have been confirmed to be ideal materials for low temperature gas detection.…”
mentioning
confidence: 99%